Effect of Larval Density on Development of the Coconut Hispine Beetle, Brontispa longissima (Gestro) (Coleoptera: Chrysomelidae) - Mika Murata; Dang Thi Dung; Shun-ichiro Takano; Ryoko Tabata Ichiki; Satoshi Nakamura (Psyche: A Journal of Entomology)
The coconut hispine beetle, Brontispa longissima shows, aggregation in the field. To elucidate the effect of aggregation on larval developmental aspects, we examined the effects of larval density on various aspects of larval development and on survival rates. Recently we found that B. longissima was divided into two monophyletic clades by genetic analysis. Therefore, we also compared the results between two populations, from Ishigaki, Japan (ISH) and Papua New Guinea (PNG), which were representative of the two monophyletic clades of B. longissima. In both ISH and PNG, the larval developmental period was shorter and the survival rate higher with rearing under high-density conditions than under isolated conditions. Similarly, fewer instars were required before pupation under high-density conditions than under isolated conditions. Brontispa longissima therefore developed better under high-density conditions, and the trends in the density effect were similar between two monophyletic clades.